Impact of Cash Holdings on Firm Value: Role of Election Induced Political Uncertainty - Omar Farooq,; Zakir Pashayev, (Asian Academy of Management Journal of Accounting and Finance, 2023)
This paper uses presidential elections as the proxy for political uncertainties to investigate the impact of election induced political uncertainties on the relationship between cash holdings and firm value for a sample of non-financial firms from the U.S. The findings suggest that the impact of cash holdings on firm value goes down significantly during the years of presidential elections. This finding, however, is confined only to elections in which both presidential candidates are new and for firms headquartered in the states that have always voted for the Democrat candidates in the presidential elections. Furthermore, our findings suggest that the impact of political uncertainties on the relationship between cash holdings and firm value does not hold for gubernatorial elections. Our results are robust after including number of firm-specific and country-specific control variables and after taking into account potential endogeneity concerns.